In Vitro: Cytotoxicity, Apoptosis and Ameliorative Potential of Lawsonia inermis Extract in Human Lung, Colon and Liver Cancer Cell Line. (20th October 2020) - Ishteyaque, Sharmeen; Mishra, Anjali; Mohapatra, Sangeeta; Singh, Aparna; Bhatta, Rabi S.; Tadigoppula, Narender; Mugale, Madhav Nilakanth
Abstract: Cancer has emerged as a major public health issue in developed as well as in developing countries. Plant-derived molecules are widely being used in the treatment of cancer due to their minimum side effects. Lawsonia inermis (Henna) is one of the medicinal plants containing many therapeutic properties. In the present study, bioactive components of L. inermis extract were analyzed by LCMS/MS method and validated. Lawsone (3.5%) is primarily responsible for cytotoxic and anti-cancerous activities. These properties were studied on human lung carcinoma (A549), colorectal cancer (DLD1) and Hepatocellular carcinoma (HepG2) cancer cell lines. The activities were assessed by MTT assay, evaluation of apoptosis by measuring the production of Reactive Oxygen Species (ROS) and mitochondrial membrane potential of the cancer cell lines. Moreover, apoptosis in the respective cancer cell lines was also determined by chromatin condensation and DNA fragmentation using Hoechst 33528 and propidium iodide (PI) staining. The preliminary in vitro result of MTT showed that the henna extract induces cytotoxic properties against A549, DLD1, HepG2 with IC50 values 490, 480 and 610 μg/ml respectively (more than 40% growth inhibition). In addition, the extract induced a concentration-dependent rise in ROS production which was 84, 102, and 110% in HepG2, DLD1 AND A549 respectively at 300 μg/ml, whereas at 400 μg/ml concentration it was 86, 102, and 106% in respective cell lines while decreasing mitochondrial membrane potential was more than 20% in the investigated cell lines. The extract also provoked changes associated with apoptosis and the data indicate that the ROS production leads to a diminution in mitochondrial membrane potential and this correlated with the extract cytotoxicity.